Historical blocking: CN 2022-08-13 to 2022-08-17 (China) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in China. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2022-0342. Severity: critical. Confidence: 95%